Review paper Intra-arterial versus intra-venous thrombolysis within and after the first 3 hours of stroke onset - Padma, Srivastava; Majaz, Moonis (Archives of Medical Science, 2010)
The NINDS trial demonstrated for the first time the effectiveness of intravenous thrombolysis in improving outcome after acute ischemic stroke. The absolute benefit of this intervention was 11-13% greater chance of being normal or near normal (MRS  1) at 3 months. However, if patients with severe stroke were considered (NIHSS  20), the absolute benefit dropped to 5-6%, indicating that IV thrombolysis may not be as effective for large vessel occlusion. This observation was further supported by TCD studies that clearly demonstrated that large artery occlusions had a recanalization rate of 13-18% with IV rt-PA. Intra-arterial thrombolysis achieves recanalization rates of 60-70%. Since tissue viability is clearly important, it is time to stop defining rigid time windows and if there is a large penumbra (20-50%) and the occlusion is in a large artery, there exists a logic and a growing evidence to consider either bridge therapy or direct intra-arterial therapy.